2021
DOI: 10.1155/2021/6624245
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Predicting Decreased Activities of Daily Living in Patients with Moyamoya Disease after Revascularization: Development and Assessment of a New Predictive Nomogram

Abstract: The aim of this study was to develop and validate a nomogram model to predict the risk of decreased activities of daily living (ADLs) in patients with moyamoya disease (MMD) following revascularization. The nomogram model was constructed based on data from 292 patients with MMD that were treated at Qilu Hospital of Shandong University from January 2018 to June 2019. The prediction model was assessed using a dataset of 119 patients with MMD collected from July 2019 to June 2020. Patients were evaluated with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We included 12 other studies that were not case reports nor case series (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). These comprised in total 1043 MMD patients (mean age: 37 years old; mean percentage of females: 58%).…”
Section: Results Of Other Studies On Psychiatric Symptoms In Moyamoya...mentioning
confidence: 99%
“…We included 12 other studies that were not case reports nor case series (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). These comprised in total 1043 MMD patients (mean age: 37 years old; mean percentage of females: 58%).…”
Section: Results Of Other Studies On Psychiatric Symptoms In Moyamoya...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%